Penerapan Hybrid Expression pada Bentuk Bangunan Sirkuit Balap Motor di Kota Lamongan - Septyo Rizky Winarto; Sigit Hadi Laksono; Ika Ratniarsih (Institut Teknologi Adhi Tama Surabaya, 2022)
In the Lamongan city area, a motorcycle racing event was held but not in the appropriate place, because the implementation was on the highway by closing the road. The place of implementation is not in accordance with the requirements for the implementation of a motorcycle racing event because of the lack of facilities and security. Most of those who carry out these activities are Generation Z youth who have character, including digital native, ambitious, instant, free spirited, critical. These activities can interfere with other road users as well as the safety of themselves and others. This circuit design aims to facilitate motorcycle racing enthusiasts to channel their hobbies more safely. The type of research used is descriptive qualitative research, this research is related to data collection to provide an overview of a symptom. The theme used in the design of the building is Contemporary Architecture with the Macro Attractive concept and the micro concept in the form of Hybrid Expression by combining the form of the Paduraksa Gate which is one of the icons of the city of Lamongan. This will be outlined in a design of the form of the building on the circuit in the city of Lamongan. is expected to be able to become a public media for competitions and add facilities for motor racing in Indonesia.